The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3390/microorganisms6040102
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Mild Heat and High-Pressure Pasteurization Against Listeria monocytogenes and Natural Microflora in Phosphate-Buffered Saline and Raw Milk

Abstract: As many as 99% of illnesses caused by Listeria monocytogenes are foodborne in nature, leading to 94% hospitalizations, and are responsible for the collective annual deaths of 266 American adults. The current study is a summary of microbiological hurdle validation studies to investigate synergism of mild heat (up to 55 °C) and elevated hydrostatic pressure (up to 380 MPa) for decontamination of Listeria monocytogenes and natural background microflora in raw milk and phosphate-buffered saline. At 380 MPa, for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…The log reduction values (TSA + YE counts) associated with 3, 6, and 9 min treated samples at 400 MPa and at 40 • C were 2.5, 3.6, and 5.2, respectively ( Figure 2B,F). This enhancement in decontamination effectiveness of a high-pressure pasteurization unit in the presence of mild heat is similar to that in recent literature, where L. monocytogenes were reduced more effectively via thermal-assisted pressure pasteurization relative to treatments of elevated hydrostatic pressure at 4 • C [25]. Results of the current study are also in harmony with the previous literature, where it has been shown that a pressure treatment at temperatures around 43 • C could lead to reductions of >5 log CFU for L. monocytogenes [18].…”
Section: Inactivation Of L Monocytogenes By High-pressure Pasteurizasupporting
confidence: 88%
See 2 more Smart Citations
“…The log reduction values (TSA + YE counts) associated with 3, 6, and 9 min treated samples at 400 MPa and at 40 • C were 2.5, 3.6, and 5.2, respectively ( Figure 2B,F). This enhancement in decontamination effectiveness of a high-pressure pasteurization unit in the presence of mild heat is similar to that in recent literature, where L. monocytogenes were reduced more effectively via thermal-assisted pressure pasteurization relative to treatments of elevated hydrostatic pressure at 4 • C [25]. Results of the current study are also in harmony with the previous literature, where it has been shown that a pressure treatment at temperatures around 43 • C could lead to reductions of >5 log CFU for L. monocytogenes [18].…”
Section: Inactivation Of L Monocytogenes By High-pressure Pasteurizasupporting
confidence: 88%
“…Treatments of hydrostatic pressure lasting for 3 min are of particular importance since currently the private industry utilizes 3-min treatments for the vast majority of commercially available products [19,20,25]. Under the condition of our experiment at 4 • C, exposure to 400 MPa of high-pressure treatments for 3 min resulted in 1.9 log CFU/mL reductions (p < 0.05) of L. monocytogenes (Figure 1A,D).…”
Section: Synergism Of Nisin Mild Heat and Elevated Hydrostatic Presmentioning
confidence: 73%
See 1 more Smart Citation
“…A four-strain mixture of L. monocytogenes (ATCC®numbers 51772, 51779, BAA-2657, and 13932), six-strain mixture of E. coli O157:H7 (ATCC®numbers BAA-460, 43888, 43894, 35150, 43889, 43890), and five-strain mixture of non-typhoidal Salmonella enterica serovars (ATCC®numbers 13076, 8387, 6962, 9270, 14028) were used in this study. The strains are selected based on preliminary data and their epidemiological and public health significance that are elaborated in detail in our recent open access publications [13][14][15][16]. These strain mixtures were used for inoculation of Cumberland river (Nashville, TN) water samples that were autoclaved for 15 min at 121 • C (MLS3781L-PA model, PHC Corporation of North America, Wood Dale, IL, USA).…”
Section: Planktonic Cells Preparations and Enumerationmentioning
confidence: 99%
“…While the effects of an array of stressors are investigated and reviewed in the literature [12], there is currently a knowledge gap for the assimilation of the effects of sub-lethal exposure to elevated hydrostatic pressure on the fate and biofilm formation of an array of microbial pathogens. This is of particular importance since the utilization of elevated hydrostatic pressure is gaining increasing importance and momentum in food manufacturing [13][14][15][16]. Information about the survival and biofilm formation of the pressure-stressed phenotype of the main microbial pathogens is critical to assure existing validation studies conducted using wild-type phenotypes are capable of controlling the pressure-stressed phenotypes of the pathogens as well.…”
Section: Introductionmentioning
confidence: 99%